Mendiagnosa Penyakit Ayam Kampung Menggunakan Metode Dempster Shafer - Virga Aulia, Ade; Pawelloi, A. Irmayani (Fakultas Teknik Universitas Muhammadiyah Parepare, 2024)
Abstract: Farm chicken breeding has become a common practice, but knowledge about chicken disease is still limited. The purpose of the research is to create an application of an expert system that helps farmers identify animal diseases according to their symptoms. The research uses a quantitative descriptive method of an expert system based on Dempster Shafer with PHP and MySQL programming languages as databases. The results of the application showed a satisfactory degree of accuracy in diagnosing diseases in village chickens. The expert system using the Dempster Shafer is a relevant solution for optimally managing livestock health. Keywords: Native Chicken; Dempster Shafer; Diagnose.